Optical coherence topography of optic nerve in sample of Iraqi population - mehdy, Dr.Imad salih; Alya Abood Kareem; Farooq Mohammed Abbas (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2019)
Background: Assessment of optic disc morphology is an important approach for detecting structural damage inpatients with glaucoma and many neurological diseases. Objective: To determine normal values of optic disc morphology measured by spectral domain opticalcoherence tomography in a sample in Iraqi population and to correlate the findings with somedemographic factors. Subjects and Method: A cross sectional study of 324 normal eyes from 162 subject aged (15-75 years) at Ibn AlHaitham teaching eye hospital in Baghdad was conducted to find the optic disc parameters (opticdisc area ,average cup disc ratio, vertical disc ratio, rim area) using the Cirrus HD OCT 5000(Zeiss Inc.).Data were collected and evaluated statistically using the independent T and Chisquare tests and a P value of less than 0.05 was considered significant. Results: Mean disc area for male was (2.2±0.5 mm2) while in female was (2.1±0.4 mm2) , the average cupdisc ratio for both male and female was (0.4±0.2) ,the vertical cup disc ratio was (0.5±0.2) forboth male and female ,the rim area was (1.5±0.5 mm2) for male while in female it was(1.4±0.4mm2) . Conclusion: Our study does not deviate largely from other studies .Intraocular pressure is important factor that affect the disc parameters even with normal range (11-21mm Hg)